2020
DOI: 10.1016/j.triboint.2020.106380
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of micro-friction and fiber orientation effects on the machinability of green composites

Abstract: This paper aims to enhance the predictiveness of a finite element (FE) model for machining of natural fiber composites through a tribological approach based on the micro-friction phenomenon between the cutting tool and the components of the composite structure. A 2D micromechanical model for orthogonal cutting of flax fibers reinforced polylactic-acid (PLA) composites is considered in this study at different orientation of fibers. Results show that the numerical thrust forces are significantly affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Attempts are being made to link the physical parameters of the lubricant, such as film thickness and viscosity, the surface roughness of surfaces in contact, the process parameters (contact pressure, sliding speed), and the elasto-plastic behavior of the interacting asperities with the amount of frictional resistance [28][29][30]. Mixed and boundary lubrication models of contact allow us to determine frictional resistances by considering the effect of load, lubricant properties and changes in sliding speed [31,32]. More complex thermo-mechanical phenomena should be taken into account during friction welding processes [33,34], which are currently of wide interest in the aerospace industry.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…Attempts are being made to link the physical parameters of the lubricant, such as film thickness and viscosity, the surface roughness of surfaces in contact, the process parameters (contact pressure, sliding speed), and the elasto-plastic behavior of the interacting asperities with the amount of frictional resistance [28][29][30]. Mixed and boundary lubrication models of contact allow us to determine frictional resistances by considering the effect of load, lubricant properties and changes in sliding speed [31,32]. More complex thermo-mechanical phenomena should be taken into account during friction welding processes [33,34], which are currently of wide interest in the aerospace industry.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…In this study, they used five different fiber orientations, as shown in Figure 5c. 43 According to the FE model and experimental findings, the cutting configuration with a fiber orientation of 65 in relation to the cutting direction provides the highest surface quality with effective shearing of flax fibers and the lowest surface roughness. 43 fabrication methods.…”
Section: Effect Of Fiber Orientation During Machining Processmentioning
confidence: 99%
“…43 According to the FE model and experimental findings, the cutting configuration with a fiber orientation of 65 in relation to the cutting direction provides the highest surface quality with effective shearing of flax fibers and the lowest surface roughness. 43 fabrication methods. Compression molding, injection molding, and Continuous Pultrusion are the close molding fabrication processes for natural composites.…”
Section: Effect Of Fiber Orientation During Machining Processmentioning
confidence: 99%
“…The presence of 0.1 micro frictions between the tool and workpiece, reduced the thrust force. 143 At both the room temperature and lower temperature, the impact of thermal and rake angle evaluated during cutting of a unidirectional flax fiber and polypropylene composite (UDF/ PP). The continuous chip formation found at any condition due to high ductility of the composite.…”
Section: Others Conventional Machiningmentioning
confidence: 99%